2019
DOI: 10.1038/s41598-019-44371-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal dysfunction on the choice of diagnostic imaging, treatment strategy, and outcomes in patients with stable angina

Abstract: We investigated the interaction between the prognostic impact of a decrease in eGFR and the choice of initial diagnostic imaging modality for coronary artery disease. Out of 2878 patients who enrolled in the J-COMPASS study, 2780 patients underwent single photon emission computed tomography (SPECT), coronary computed tomography (CT) angiography, or coronary angiography (CAG) as an initial diagnostic test. After excluding patients with routine hemodialysis or lacked serum creatinine levels, 2096 patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The results are expressed as HRs and 95% CIs. There are several sources of bias in the processes of referral for angiography, performance of coronary revascularisation and revascularisation strategy, that could have influenced the risk of revascularisation in the patients who had SPECT and those who had CT. To overcome these sources of bias, we selected sixteen clinically relevant risk-adjusting variables as well as the severity of abnormal findings and the treatment strategies in each group: age ≥60 years; sex; body mass index (BMI); estimated glomerular filtration rate; the presence of hypertension, dyslipidaemia, diabetes, hyperuricaemia, chronic obstructive pulmonary disease and atrial fibrillation; Canadian Circulation Society class 2 or higher 8 ; current smoking status; New York Heart Association functional class 2 or higher 9 which is consistent with that used in our previous reports [2][3][4] ; severity of abnormal findings (SSS ≥8 or three vessel disease); escalation of medical therapy; and early revascularisation (table 1). We then tested the interaction between the prognostic impact of early revascularisation and each diagnostic modality.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results are expressed as HRs and 95% CIs. There are several sources of bias in the processes of referral for angiography, performance of coronary revascularisation and revascularisation strategy, that could have influenced the risk of revascularisation in the patients who had SPECT and those who had CT. To overcome these sources of bias, we selected sixteen clinically relevant risk-adjusting variables as well as the severity of abnormal findings and the treatment strategies in each group: age ≥60 years; sex; body mass index (BMI); estimated glomerular filtration rate; the presence of hypertension, dyslipidaemia, diabetes, hyperuricaemia, chronic obstructive pulmonary disease and atrial fibrillation; Canadian Circulation Society class 2 or higher 8 ; current smoking status; New York Heart Association functional class 2 or higher 9 which is consistent with that used in our previous reports [2][3][4] ; severity of abnormal findings (SSS ≥8 or three vessel disease); escalation of medical therapy; and early revascularisation (table 1). We then tested the interaction between the prognostic impact of early revascularisation and each diagnostic modality.…”
Section: Discussionsupporting
confidence: 84%
“…It is important to choose the appropriate initial diagnostic imaging modality to detect coronary artery disease (CAD) in symptomatic patient. [1][2][3][4] Although the superiority of anatomical testing over functional testing has long been discussed, compared to initial functional testing, anatomical testing strategies using CT do not reduce the incidence of major adverse cardiac events (MACEs). 1 2 4 Douglas et al reported that patients who had initial anatomic testing using CT underwent revascularisation more frequently than those who had initial functional testing.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes included major adverse cardiovascular event (MACEs), such as death, acute MI, hospitalization for heart failure, and late revascularization (>3 months) in accordance with the original and sub-studies 9,[12][13][14] . A 1-year follow-up was performed with an allowance of 1 month.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The diagnosis of coronary artery disease (CAD) and early intervention in symptomatic patients with suspected CAD is challenging [ 7 ], and its definitive diagnosis in clinical practice remains complicated [ 8 ]. Although current methods reduce the probability of misdiagnosis of stable CAD, the invasive diagnostic procedures used can be considered an overly medical approach.…”
Section: Introductionmentioning
confidence: 99%